Poprawna interpretacja kan. 538 § 3 i kan. 1110 z Kodeksu Jana Pawła II. Dwa zapytania z Krakowa do Papieskiej Rady ds. Tekstów Prawnych - Rozkrut, Tomasz (Ius Matrimoniale, 2020)
This article presents two inquiries directed to the Pontifical Council for Legislative Texts by canonists from Cracow. The presentation in question was preceded by synthetic indication of rules for performing interpretation of the Church’s law, specifically the role of the Pontifical Council for Legislative Texts. This special Dicastery of the Roman Curia also provides answers to numerous inquiries, thus providing assistance to various authorities and individual people of faith in interpreting norms that are, basically obvious, but that raise doubts. In such cases it is used to clarify the arose doubt and contributes to correct interpretation of the existing law in practice. It arises from the provided answers that the institution of parish priest is regarded as stable, which is clearly stated in can. 522 of the Code of Canon Law. One of the elements that are a guarantor of the parish priest institution, though not listed outright by the general legislator, is a possibility to remain in the position until one reaches seventy five years of age. This also confirms that this age, that is determined in the Code, cannot be changed by the particular legislator in any valid manner. Thus, also the possible customs in a given Diocese that were introduced after John Paul II promulgated the post-conciliar code in 1983 that are in contradiction to provisions included in that Code must be regarded as erroneous, as they are not in line with can. 26. Explanation provided by the Pontifical Council for Legislative Texts in regards to the arose doubt of a possibility to grant delegation by a personal parish priest to bless canonical marriage also occurred to be important in practice. Likewise territorial parish priest, personal parish priest has identical authorizations in this matter. As it can be observed, the Pontifical Council for Legislative Texts provides very useful and competent help in solving various legal doubts that are of great importance for functioning of the Church. If even before getting competent answers a large number of canonist had similar views to those presented in explanations, which was actually demonstrated, then the answers provided by the Vatican indicate a definitive solutions to the arose doubts and at the same time encourage those who – assuredly not out of ill will –succumbed to very subjective and erroneous interpretation, to correct it.